Variants in Adjacent Oxytocin/Vasopressin Gene Region and Associations with ASD Diagnosis and Other Autism Related Endophenotypes - Francis, Sunday M.; Kistner-Griffin, Emily; Yan, Zhongyu; Guter, Stephen; Cook, Edwin H.; Jacob, Suma (Frontiers in Neuroscience, 2016)
Background: There has been increasing interest in oxytocin (peptide: OT, gene: OXT) as a treatment pathway for neurodevelopmental disorders such as Autism Spectrum Disorder (ASD). Neurodevelopmental disorders affect functional, social, and intellectual abilities. With advances in molecular biology, research has connected multiple gene regions to the clinical presentation of ASD. Studies have also shown that the neuropeptide hormones OT and arginine vasopressin (AVP) influence mammalian social and territorial behaviors and may have treatment potential for neurodevelopmental disorders. Published data examining molecular and phenotypic variation in ASD, such as cognitive abilities, are limited. Since most studies have focused on the receptors in the OT-AVP system, we investigated genetic variation within peptide genes for association with phenotypic ASD features that help identify subgroups within the spectrum. Methods: In this study, TDT analysis was carried out utilizing FBAT in 207 probands (156 trios) and a European Ancestry (EA) subsample (108 trios). The evolutionarily related and adjacent genes of OXT and AVP were studied for associations between the tagged single nucleotide polymorphisms and ASD diagnosis, social abilities, restrictive and repetitive behaviors, and IQ for cognitive abilities. Additionally, relationships with whole blood serotonin (WB5HT) were explored because of the developmental relationships connecting plasma levels of OT and WB5HT within ASD. Results: Results indicate significant association between OXT rs6084258 (p=0.001) and ASD. Associations with several intermediate phenotypes were also noted: OXT rs6133010 was associated with IQ (full scale IQ, p=0.008; nonverbal IQ, p=0.010, verbal IQ, p=0.006); and OXT rs4813625 and OXT rs877172 were associated with WB5HT levels (EA, p=0.027 and p=0.033, respectively). Additionally, we measured plasma OT (pOT) levels in a subsample (N=54). Results show the three polymorphisms, OXT rs6084258, OXT rs11697250, and OXT rs877172, have significant association with pOT (EA, p=0.011, p=0.010, and p=0.002, respectively). Conclusions: These findings suggest that SNPs near OXT and AVP are associated with diagnosis of ASD, social behaviors, restricted and repetitive behaviors, IQ, pOT, and WB5HT. Future studies need to replicate these findings and examine gene-interactions in other neurodevelopmental disorders. Mechanisms of action may influence early social and cognitive development that may or may not be limited to ASD diagnosis.